"Stacking" or "picking" patents? The inventors' choice between quality and quantity - Myriam Mariani; Marzia Romanelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
This paper studies the determinants of the quantity and quality of inventors' patents. It uses a sample of 793 inventors drawn from the PatVal-EU dataset and the information on EPO patents that they contributed to inventing during the period 1988-1998. It explores three aspects of the inventors' productivity: 1) the number of EPO patents that they produce; 2) their average quality; 3) the quality of the most valuable patents. By jointly estimating the three equations we find that the inventors' level of education, employment in a large firm and involvement in large-scale research projects positively affect quantity. Yet, apart from the size of the research project, none of these factors directly influences the expected quality of the innovations. They do, however, indirectly, as we find that the number of innovations explains the probability of producing a technological hit (the maximum value). Also, there are no decreasing returns in the innovation process at an individual level, as the number of innovations that an inventor produces is not correlated with their average quality.
Keywords: 330; Erfindung; Patent; EU-Staaten